Adverse childhood experiences and past 30-day cannabis use among middle and high school students: The protective influence of families and schools. (July 2022) - Clements-Nolle, Kristen D.; Lensch, Taylor; Drake, Cara S.; Pearson, Jennifer L.
Highlights: There was a strong graded relationship between ACEs and past 30-day CU. Family communication had an independent relationship with past 30-day CU. School connectedness had an independent relationship with past 30-day CU. Findings support the compensatory model of resiliency. Abstract: Exposure to adverse childhood experiences (ACEs) is a risk factor for adolescent cannabis use (CU). We explored whether family communication and school connectedness can offer direct protection (the compensatory model of resiliency) or moderating protection (the protective factors model of resiliency). Using cluster random sampling, a Youth Risk Behavior Survey (YRBS) was conducted with 5, 341 middle school and 4, 980 high school students in 2019. Generalized estimating equations were used to estimate whether family communication and school connectedness offered independent direct protection (multiple regression) or moderating protection (multiplicative interaction) in the relationship between ACEs and past 30-day CU. Adjusted prevalence ratios (APR) and 95% confidence intervals (95% CI) were calculated. There was a graded relationship between ACEs and past 30-day CU for all students that was particularly strong among middle school students: 1 ACE (APR = 2.37, 95% CI = 2.16, 2.62), 2 ACEs (APR = 2.89, 95% CI = 2.60, 3.23), 3 ACEs (APR = 5.30, 95% CI = 4.75, 5.90), 4 + ACEs (APR = 7.86, 95% CI = 7.13, 8.67). Results supported the compensatory model of resiliency with both family communication (middle school APR = 0.90, 95% CI = 0.88, 0.93; high school APR = 0.90, 95% CI = 0.87, 0.93) and school connectedness (middle school APR = 0.76, 95% CI = 0.72, 0.79; high school APR = 0.72, 95% CI = 0.68, 0.77) demonstrating a direct, independent protective relationship with past 30-day CU. There was no consistent evidence supporting the protective factors resiliency model.